The Harcourt Brace student thesaurus - Morris, Christopher; Harcourt Brace & Company (San Diego : Harcourt Brace & Co., 1994)
Contains synonyms and antonyms arranged alphabetically with an index of synonyms not in the main alphabetical listing.
Includes index.
Updated ed. of: The HBJ student thesaurus.
Elem. School Library Collection.
School Library Journal.
Wilson's Children.
5.5.
Keywords: English language -- Synonyms and antonyms -- Juvenile literature; English language -- Synonyms and antonyms; English language -- Synonyms and antonyms